Characterization of microtubule buckling in living cells - Pallavicini, Carla (2017)
Microtubules are filamentous biopolymers involved in essential biological processes. They form key structures in eukaryotic cells, and thus it is very important to determine the mechanisms involved in the formation and maintenance of the microtubule network. Microtubule bucklings are transient and localized events commonly observed in living cells and characterized by a fast bending and its posterior relaxation. Active forces provided by molecular motors have been indicated as responsible for most of these rapid deformations. However, the factors that control the shape amplitude and the time scales of the rising and release stages remain unexplored. In this work, we study microtubule buckling in living cells using Xenopus laevis melanophores as a model system. We tracked single fluorescent microtubules from high temporal resolution (0.3–2 s) confocal movies. We recovered the center coordinates of the filaments with 10-nm precision and analyzed the amplitude of the deformation as a function of time. Using numerical simulations, we explored different force mechanisms resulting in microtubule bending. The simulated events reproduce many features observed for microtubules, suggesting that a mechanistic model captures the essential processes underlying microtubule buckling. Also, we studied the interplay between actively transported vesicles and the microtubule network using a two-color technique. Our results suggest that microtubules may affect transport indirectly besides serving as tracks of motor-driven organelles. For example, they could obstruct organelles at microtubule intersections or push them during filament mechanical relaxation.